2017
DOI: 10.7566/jpsj.86.113701
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Supermodulation in LaO0.5F0.5BiSe2 by Scanning Tunneling Microscopy and Spectroscopy

Abstract: We observed surface and electronic structure of LaO 0.5 F 0.5 BiSe 2 single crystal by scanning tunneling microscopy/spectroscopy (STM/STS) at 4.2 K. Square lattice composed of Bi atoms was observed at a positive sample bias voltage on the surface prepared by cleavage. At a negative sample bias voltage, a stripe structure running along Bi-Bi directions was observed as in the previous report on NdO 0.7 F 0.3 BiS 2 . Furthermore, we observed a supermodulation running along the diagonal directions with the period… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Using single crystals, scanning tunneling microscopy/spectroscopy (STM/STS) has been performed to analyze the surface structure and the electronic states of BiS 2 -based compounds [58,75,158,200]. Machida et al observed checkerboardstripe electronic states for NdO 0.7 F 0.3 BiS 2 [75].…”
Section: Spectroscopymentioning
confidence: 99%
“…Using single crystals, scanning tunneling microscopy/spectroscopy (STM/STS) has been performed to analyze the surface structure and the electronic states of BiS 2 -based compounds [58,75,158,200]. Machida et al observed checkerboardstripe electronic states for NdO 0.7 F 0.3 BiS 2 [75].…”
Section: Spectroscopymentioning
confidence: 99%
“…In addition, some Bi defects have dark streaks along one or two diagonal directions of the Bi square lattice. The density of defects was about 1% and was almost the same as that in x = 0.5 sample [4]. Thus, the Bi defect density is almost independent of the amount of F. Figure 1 (b) shows the STM image taken at a negative sample bias voltage for the same field of view as Figure 1 (a).…”
Section: Methodsmentioning
confidence: 73%
“…However, spectroscopic gap was observed at the Fermi energy EF despite of metallic bulk properties [2]. Furthermore, the unexpected supermodulation with the period of about 5 times the length of the lattice constant running along the diagonal direction of the Bi square lattice was revealed in LaO0.5F0.5BiS2 (x = 0.5) single crystals by synchrotron X-ray measurements [3] and in LaO0.5F0.5BiSe2 (x = 0.5) single crystals by STM/STS measurements [4]. Theoretically, in high F doping samples, such as LaO0.5F0.5BiS2 (x = 0.5), the phonon instability spreading from near Γ point to M point is predicted while in low F doping samples, such as LaOBiS2 (x = 0), the phonon instability around Γ point is predicted [5].…”
Section: Introductionmentioning
confidence: 99%